Maintenance Financing and Its Impact on Road Performance: A Case Study of Mugling-Narayanghat-Lothar Section, Nepal - Khadka, Bimal; Bist, Trilok Chandra (Journal of Engineering Technology and Planning, 2025)
Nepal’s Strategic Road Network (SRN) forms the backbone of national connectivity and economic integration. By February 2024, Nepal’s national road network come to 34,257 km, including 18,421 km of blacktopped roads, 7,697 km of gravel roads, and 8,139 km of earthen roads. The maintenance of roads continues to suffer from chronic underfunding and weak institutional management. This study aims to evaluate the allocation and sufficiency of funds for SRN maintenance, identify shortcomings, and suggest improvements focusing on the Mugling–Narayanghat–Lothar corridor under the Bharatpur Division Road Office. A mixed-method approach was employed, integrating secondary data from the Roads Board Nepal (RBN), Department of Roads (DoR), and Division Road Offices with Key Informant Interviews (KII) and Focus Group Discussions (FGD) involving engineers, financial officers, and experts. The findings reveal a significant fund deficit, with a shortfall of NRs. 77.73 billion (70.53%) in Strategic Road Network maintenance funding by FY 18/19, and a 51.59% deficit in the Mugling-Narayanghat-Lothar section between FY 13/14 and 17/18. The major challenges include insufficient budget allocation by the Ministry of Finance, improper distribution of revenue collected from road users, and the lack of a performance-based fund disbursement mechanism by the Road Board Nepal. The study recommends revising ARMP based on proper assessments and allocating funds equitably based on user charge contributions. Despite significant revenue generation from fuel levies and vehicle registration fees, only a small portion was allocated to RBN. Key challenges include limited budget allocation, incomplete transfer of road user revenues, manpower shortages, and reliance on traditional maintenance practices. The study recommends ensuring all revenues transfer to RBN, adopting the PBMC approach, integrating maintenance into life cycle cost planning, and establishing a research and development.